2019
DOI: 10.1155/2019/1498034
|View full text |Cite
|
Sign up to set email alerts
|

Rs2015 Polymorphism in miRNA Target Site of Sirtuin2 Gene Is Associated with the Risk of Parkinson’s Disease in Chinese Han Population

Abstract: Accumulating evidence reveals that the sirtuin family is involved in the pathology of Parkinson’s disease (PD). However, the association between the polymorphisms of the sirtuin gene and the risk of PD remains elusive. Here, we investigated the possible association of nine SIRT1 and SIRT2 SNPs with the risk of PD through a clinical case-control study from the Chinese Han population. Our results showed that rs12778366 in the promoter region of SIRT1 and rs2015 in the 3′untranslated region (3′UTR) of the SIRT2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
1
14
1
1
Order By: Relevance
“…Second, an increase in SIRT2 levels has been described in different neuropsychiatric and neurodegenerative diseases including AD [ 29 , 39 ], PD [ 50 , 59 , 60 , 61 ], and Huntington’s disease (HD) [ 62 ], both in mouse models and human postmortem brain tissues ( Table 2 ). Moreover, SIRT2 deletion or pharmacological inhibition has provided beneficial effects in different neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Second, an increase in SIRT2 levels has been described in different neuropsychiatric and neurodegenerative diseases including AD [ 29 , 39 ], PD [ 50 , 59 , 60 , 61 ], and Huntington’s disease (HD) [ 62 ], both in mouse models and human postmortem brain tissues ( Table 2 ). Moreover, SIRT2 deletion or pharmacological inhibition has provided beneficial effects in different neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this study reported down-regulated SIRT1 expression, and up-regulated SIRT2 mRNA level in PD patients as compared to non-PD controls. These gene expression changes correlated with the presence of the rs12778366 of SIRT1 and r2015 of SIRT2 variants 21 . Results of a meta-analysis by Nicholatos et al .…”
Section: Introductionmentioning
confidence: 82%
“…In recent years a growing body of evidence has accumulated on the importance of SIRTs in PD pathogenesis 6 . SIRT1 and SIRT2 seem to have opposite effects on the development and course of the disease 21 . A recent meta-analysis revealed strong association between SIRT6 polymorphisms and PD, suggesting a pathogenic role of SIRT6 in the disease 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have corroborated that specific SIRT2 single-nucleotide polymorphisms (SNPs) correlate to the risk of a number of neurodegenerative diseases, like Alzheimer's disease (AD) (Polito et al, 2013;Porcelli et al, 2013;Xia et al, 2014;Cacabelos et al, 2019;Shen et al, 2020) and Parkinson's disease (PD) (Wang et al, 2018;Chen et al, 2019) under certain conditions. Recent studies demonstrated that SIRT2 participates in even more pathological processes such as frontotemporal dementia (FTD) (Spires-Jones et al, 2012), stroke (Shu et al, 2019), and brain injury (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 96%